A blinded, randomized, placebo-controlled prospective study of the impact of the effect of photobiomodulation therapy in dogs with cranial cruciate ligament rupture after TPLO surgery - Chavez Zamora, Oscar Alejandro (Kansas State University, 2023)
Objective: Effect of photobiomodulation therapy (PBMT) in patients with CCLR after TPLO surgery by measuring C-reactive protein, percentage weight bearing, lameness using a short form of a composite measure pain scale, evaluated by the clinician and owners, and surgical site infection. Sample population: 54 client-owned dogs with CCLR undergoing unilateral TPLO surgery were enrolled in this study between April 5, 2021 – April 10, 2022. Methods: The study population was randomly assigned to either a treatment group receiving PMBT (24 dogs) or control group (30 dogs). PMBT was performed on the treatment group immediately after induction, and 6 hours, 24 hours, 48 hours and 8 weeks post-operatively. The control group received sham PMBT (device turned off) same time. Evaluation of CRP, CMPS-SF, evidence of SSI, and %WB were evaluated for all dogs 24 hours pre-operatively, and then 24 hours, 48 hours, and 8 weeks post-operatively. Owners completed CMPS-SF and subjective evaluations weekly for 8 weeks post-operatively. Results: No statistically significant differences were found between treatment groups when evaluating CRP, %WB and CMPS-SF by clinician and weekly evaluation of the CMPS-SF by owners. Although no statistically significant differences were found on patients developing surgical site infections between treatment groups, SSI were only observed in patients in the control group (5/30, 16.6%). Most were minor/superficial infections (4/30 13.3%), and a single dog (1/30, 3.3%) had a major/deep surgical site infection. Clinical relevance: Although with promising but not statistically significant differences between groups, surgical site infections may be reduced after PBMT application.
Keywords: Photobiomodulation therapy (PBMT); Tibial plateau leveling osteotomy (TPLO); Cranial cruciate ligament rupture (CCLR); C reactive protein (CRP); Light amplification by stimulated emission of radiation (LASER)